North American Natural Gas Supply Forecast: The Hubbert Method Including the Effects of Institutions - Marek Kolodziej; Douglas B. Reynolds (Energies, 2009)
In this article, the U.S. and southern Canadian natural gas supply market is considered. An important model for oil and natural gas supply is the Hubbert curve. Not all regions of the world are producing oil or natural gas following a Hubbert curve, even when price and market conditions are accounted for. One reason is that institutions are affecting supply. We investigate the possible effects of oil and gas market institutions in North America on natural gas supply. A multi-cycle Hubbert curve with inflection points similar to the Soviet Union’s oil production multi-cycle Hubbert curve is used to determine North American natural gas discovery rates and to analyze how market specific institutions caused the inflection points. In addition, we analyze the latest shale natural gas projections critically. While currently, unconventional resources of natural gas suggest that North American natural gas production will increase without bound, the model here suggests a peak in North American natural gas supplies could happen in 2013.